Kata Jion Training's For Karate Coach - Arie Asnaldi; Hilmainur Syampurma; Puput Sekar Sari (Universitas Negeri Padang Press, Pusat Kajian Pendidikan Olahraga, Kesehatan dan Rekreasi, Fakultas Ilmu Keolahragaan, Univeristas Negeri Padang., 2021)
In sports coaching achievements should coaches, athletes and team managers understand the elements that can affect achievement that include physical condition, technique, tactics, and mental. In coaching the achievements of coaches are required not only to train physical conditions and techniques, but also must pay attention as well as the tactics and mentality of athletes. But seen the reality on the ground in saying athletes who are a sportsman who participates in a race or match in the field of sports and have achievements are still very weak in understanding and showing skills in the management of moves said Jion. The goal to be achieved from this activity is that the pealtih are able in theory and practice in developing their abilities, especially the ability to show mastery of the moves said Jion. In addition, the coaches are expected to have the ability to expand their horizons by utilizing the maximum science and technology that is growing very rapidly. The approach method offered in problem solving is to use the lecture method to convey techniques or moves in performing the word jion, direct discussion with the target audience, Training or debriefing knowledge of the word jion, Training / demonstration about the practice of technique of the word jion and mentoring and evaluation of trainees in the field. Based on the test results, the average karateka coach who participated in this training activity, had an improvement in knowledge and skills. With this result, it is expected that all coaches can train better and correctly and professionally. So that it can produce athletes who excel at the local, regional, national and even international levels.